2000
DOI: 10.1159/000022158
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Osteoporosis in Elderly Women

Abstract: Objectives: To study body composition in elderly osteoporotic women to determine the relationship of body weight, body fat mass and lean mass to bone mineral density (BMD), and to investigate the association between one-leg balance, osteoporosis and sarcopenia. Design and Setting: A cross-sectional study of a community-based population in Toulouse, France. Methods: For each participant, whole body composition and BMD were estimated using a dual-energy x-ray absorptiometry scanner. We investigated balance using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
3
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 23 publications
3
50
3
3
Order By: Relevance
“…In addition, BMD had a statistically significant positive correlation with body weight and BMI. Furthermore, the results of the current study revealed that BMD was significantly positively correlated with regional fat percentage (higher values of fat mass may have a protective effect on bone density [5]). However, when logistic regression analysis was done, regional fat failed to show an independent effect on low BMD, while total body weight was protective against low BMD.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In addition, BMD had a statistically significant positive correlation with body weight and BMI. Furthermore, the results of the current study revealed that BMD was significantly positively correlated with regional fat percentage (higher values of fat mass may have a protective effect on bone density [5]). However, when logistic regression analysis was done, regional fat failed to show an independent effect on low BMD, while total body weight was protective against low BMD.…”
Section: Discussionsupporting
confidence: 51%
“…Women with more body fat have lower rates of bone resorption (an independent predictor of fracture) during menopause than women with less body fat [3]. In women, bone mineral status is much more closely associated with total body fat [4] and in a multivariate model total fat mass alone was correlated with whole body BMD [5].…”
Section: Introductionmentioning
confidence: 98%
“…In our sample, the heritability estimates for peak BMD in the spine, femoral neck, and hip are 0.565, 0.702, and 0.693, respectively. Second, we have now learned that lean mass and fat mass may be important determinants of the BMD [45,46] . Many previous studies used BMD as a surrogate marker of bone strength, which did not take into account determinants of bone strength (eg, fat mass, lean mass and PFM) other than bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a total body fat mass assessed by DXA in postmenopausal women could predict BMD at the spine and at the hip. The decreased fat mass is a risk factor for osteoporotic fractures, because 11% to 15% of patients with fragility fractures showed low fat mass, whereas the lean body mass in the same patients remained the same compared to controls; in women aged more than 75 years, a protective effect of body weight and fat mass on BMD at several skeletal sites was positively correlated with the weight and the fat mass (Gillette-Guyonnet et al, 2000). A swedish study, on the other hand, compared urban and rural populations and found that the incidence of osteoporotic fractures was higher only in a group of women more than 70 years old with reduced muscle mass, which highlighted the importance of the muscle mass as a primary agent influencing the bone mass changes and the fracture risk in elderly women (Elmstahl et al, 1993).…”
Section: Contribution Of Lean and Fat Mass To Bone Massmentioning
confidence: 97%
“…It was concluded that the lean body mass has a protective effect on BMD at the femoral neck (Gillette-Guyonnet et al, 2000). So far, it is unclear whether lean mass regulates the bone mass in the postmenopausal women.…”
Section: Wwwintechopencommentioning
confidence: 99%